Upgrading gSeaGen: from MeV to PeV neutrinos. (10th September 2021) - Garcia Soto, A.; Distefano, C.; Kalaczyński, P.
Abstract: The gSeaGen framework has been upgraded to simulate events detectable in neutrino telescopes induced by neutrino or cosmic ray interactions. The new version is well-suited to generate neutrino interactions at energies from a few MeV to EeV, profiting from the latest GENIE extensions to lower and higher energies. In addition, a brand new functionality to propagate leptons from CORSIKA air showers has been developed. Novel features of gSeaGen will be presented, related to simulation of PeV tau neutrinos and charged lepton propagation, using the KM3NeT detectors as physics case.